A Critical Analysis of South Africa’s System of Government: From a Disjunctive System to a Synergistic System of Government - Mhlongo, Lindelwa (Obiter, 2020)
The right to vote in South Africa is one of the fundamental rights recognised by the Constitution. South Africa ran its sixth election on 8 May 2019. Since the birth of democracy in 1994, it has had four presidents, two of whom did not serve their full term in office. Former President Thabo Mbeki resigned after he was recalled for using the country’s law enforcement system to undermine Jacob Zuma’s chances of succeeding him. He resigned with nine months to go in his second term in office. Mbeki’s successor, former President Jacob Zuma, also resigned from office during his second term with 14 months to go. Several stinging criticisms were levelled against him. For example, he was accused of tribalism and being a “ruralitarian” who lacked urban sophistication to understand and lead a large economy such as South Africa. He was also accused of benefiting his family through creating business opportunities for them and directing development projects to his home village. Furthermore, his government was accused of being weak on corruption, and being easily influenced by the communists. In light of the above, the question that begs for an answer is: does the current South African system of government and electoral system provide for high-level political accountability? In answering this question, further ancillary questions are posed throughout the article. What informed the drafters of the Electoral Amendment Act 73 of 1998 to choose the current electoral system? Is it time for South Africa to review its electoral system? How can South Africa increase the level of political accountability of the President?